1984
DOI: 10.1111/j.1432-1033.1984.tb08537.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a novel polysaccharide isolated from Zymomonas mobilis determined by nuclear magnetic resonance spectroscopy

Abstract: A novel polysaccharide has been observed in uivo by 13C nuclear magnetic resonance (NMR) spectroscopy of the gram-negative bacterium, Zymomonas mobilis. The polysaccharide, which was not removed from the Zmobilis cell by washing with 0.86 % saline, was extracted by mild acid treatment. The structure was elucidated by a combination of NMR techniques, including proton and proton-carbon two-dimensional methods. The structure was determined to be -a-fructofuranosyl-(2-1)-~-fructofuranosyl-(2-6)-. The polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…It is well established that the maximum value of Y ETOH in Z. mobilis catabolism under anaerobic conditions is close to 0.51 g of ethanol per gram of consumed glucose [18,21], and that under aerobic growth conditions Y ETOH is lower due to competition for NADH between the respiratory chain and ethanol synthesis [15]. In the aerobic chemostat culture of the mutant strain, we found Y ETOH to be 0.22 g g À1 , which constitutes 43% of the maximum value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the maximum value of Y ETOH in Z. mobilis catabolism under anaerobic conditions is close to 0.51 g of ethanol per gram of consumed glucose [18,21], and that under aerobic growth conditions Y ETOH is lower due to competition for NADH between the respiratory chain and ethanol synthesis [15]. In the aerobic chemostat culture of the mutant strain, we found Y ETOH to be 0.22 g g À1 , which constitutes 43% of the maximum value.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized that the measured bulk reactant ratios for the ADH reaction in both strains were closely similar, generally exceeding K eq by 3 orders of magnitude, and hence could not explain the extremely different responses of the strains to the ethanol pulse. Taking the measured values for ethanol, acetaldehyde and intracellular NADH concentrations (Table 2), 6.5 for intracellular pH [18], 3.3 ll per mg of dry weight for the intracellular volume [19], and (for the lowest estimate of the reactant ratios) assuming that NAD + makes up most of the 5 mM intracellular NAD(P)(H) pool, detected in Z. mobilis by NMR [20], we come to reactant ratios of 2.6 · 10 À9 M for ZM6 and 12.6 · 10 À9 M for the ADH II-deficient strain. These are indeed the lowest estimates of the reactant ratios, because: (i) by assuming the intracellular acetaldehyde/ethanol ratio equal to that of the outer medium, we are neglecting the fact that acetaldehyde is a more volatile compound than ethanol, and hence, the true intracellular acetaldehyde/ethanol ratio might be higher; (ii) a lower value for the intracellular volume of Z. mobilis has been reported by Osman et al [21], which would result in a higher measured intracellular NADH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with the published 13 C chemical shifts of fructan produced by Lb. reuteri strain 121 grown on MRSr media [8] and Z. mobilis levan [14] indicated that the FTF fructan had a [C6)-L-D-Fruf-(2C] n structure, a levan. Further con¢r-mation was obtained from the identical 1 H NMR spectra of the FTF fructan (results not shown) and the fructan produced by MRSr grown Lb.…”
Section: In Vitro Fructan Production and Fructan Analysismentioning
confidence: 99%
“…Inocula (5% in volume) were grown for 18 h in stationary flasks. Cultures were run at 30°C in a 2-liter fermentor containing 1.5 liters of medium with mild agitation (200 rpm), and pH was controlled at 5.5 by addition of 2 subtilis levans (average molecular mass, 15,000 daltons) per ml and the enzyme solution. Aliquots of 10 Al were taken every 30 min (for 2 h) and treated as above for the exchange reaction.…”
Section: Materials and Methods Bacterial Strains And Plasmids Eschermentioning
confidence: 99%